2023
DOI: 10.51744/crpp7
|View full text |Cite
|
Sign up to set email alerts
|

Seeds for recovery: The long-term impacts of a complex agricultural intervention on welfare, behaviour and stability in Syria (SEEDS)

Abstract: There is scarce evidence on whether and how assistance in humanitarian emergencies and conflict settings impacts household well-being and behaviour. Conducting rigorous impact evaluations in such settings poses multiple challenges in design and data collection. In SEEDS, we evaluate the impact of a complex large-scale multi-arm agricultural intervention on productivity, food security, and resilience in the context of an on-going humanitarian crisis in Syria. Specifically, we identify the causal impacts of agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In one evaluation, claims about equity over the longer term relied on a methodological innovation that applied machine learning to a combination of panel data about households and their socio-economic position and satellite data about the agricultural productivity of communities (Baliki et al, 2023). This study found that 'female-headed households benefit remarkably more in terms of food security in the medium-term compared to male-headed families' (p. 3).…”
Section: Phase Ii: Focus Of Claims About Developing Effective Complex...mentioning
confidence: 99%
See 4 more Smart Citations
“…In one evaluation, claims about equity over the longer term relied on a methodological innovation that applied machine learning to a combination of panel data about households and their socio-economic position and satellite data about the agricultural productivity of communities (Baliki et al, 2023). This study found that 'female-headed households benefit remarkably more in terms of food security in the medium-term compared to male-headed families' (p. 3).…”
Section: Phase Ii: Focus Of Claims About Developing Effective Complex...mentioning
confidence: 99%
“…A study of complex agricultural interventions acknowledged the potential impact of environmental shocks, such as hyperinflation, drought, violent conflict, and COVID-19, although without detailing exactly their influence in a theory of change (Baliki et al, 2023). Nevertheless, this study illustrated the importance of taking into account context, finding that 'households residing in areas that are moderately affected by violent conflict show stronger food security improvements [following complex agricultural interventions] compared to households from peaceful or conflict-intense settings' (p 7).…”
Section: Phase Ii: Scope Of Claims In Terms Of Certainty and Reachmentioning
confidence: 99%
See 3 more Smart Citations